2015
DOI: 10.1111/bjd.14075
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated cytokine expression in lesional and nonlesional skin in hidradenitis suppurativa

Abstract: SummaryBackground There is a dearth of information on the precise pathogenesis of hidradenitis suppurativa (HS), but immune dysregulation is implicated. Objectives To determine the nature of the immune response in HS. Methods Skin biopsies -lesional, perilesional (2 cm away) and uninvolved (10 cm away) -were obtained from patients with HS and healthy controls. The expression of various cytokines was determined by enzyme-linked immunosorbent assay, flow cytometry and real-time polymerase chain reaction. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
264
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(299 citation statements)
references
References 36 publications
13
264
0
5
Order By: Relevance
“…Also overexpression of macrophages producing IL-12 and IL-23, and IL-17-producing cells were found in lesional HS skin [18]. These results were recently confirmed by Kelly et al [19]. They also demonstrated activated caspase-1 in HS skin, which is associated with IL-1b and IL-18 production.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Also overexpression of macrophages producing IL-12 and IL-23, and IL-17-producing cells were found in lesional HS skin [18]. These results were recently confirmed by Kelly et al [19]. They also demonstrated activated caspase-1 in HS skin, which is associated with IL-1b and IL-18 production.…”
Section: Introductionsupporting
confidence: 65%
“…They also demonstrated activated caspase-1 in HS skin, which is associated with IL-1b and IL-18 production. These results suggest that the IL-23/Th17 and the caspase-1 pathways play an important role in the pathogenesis of HS [17][18][19].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…33 A recent study demonstrated enhanced mRNA expression of TNF-α in lesional and perilesional HS skin, but it was less pronounced than the increase of IL-17 and IL-1beta. 33,35 Furthermore, the proinflammatory cytokines IL-12 and IL-23 are abundantly expressed by macrophages infiltrating papillary and reticular dermis in HS. 36 A subclinical inflammatory state occurs in the skin prior to the onset of a visibly active HS.…”
Section: 1-inflammationmentioning
confidence: 99%
“…A szövet-tani minták elemzésének másik szembetűnő lelete az acné-ből jól ismert follicularis hiperkeratinizáció/okklúzió volt, mely a folliculusok kitágulásához majd roncsolódásához vezet, így a baktériumokban gazdag törmelék a dermist infiltrálva annak gyulladását eredményezi felvetve, hogy a baktériumok és a különböző gyulladásos útvonalak éppúgy fontosak lehetnek ebben a betegségben is (1. ábra). A gyulladásban szerepet játszó sejteken az acnéban ismerthez hasonlóan, szintén fokozottan vannak jelen a Toll-like receptorok (TLR) (3), illetve a legfrissebb teljes szöveti mintákon elvégzett génexpressziós analízisek a TNF-α, IL-1 és a NOD-like receptor (NLRP) gének/útvonalak fokozott kifejeződését találták (4), melyek szerepét a genetikai vizsgálatok során azonosított egy nukleotidos polimorfizmusok (SNP) is alátámasztottak (5). Ezek alapján jogos az igény a lehetőségeinkhez mért tisztánlátásra, valamint hogy azonosítsuk azokat a faktorokat, melyek a HSben szerepet játszanak akár arra specifikusan, akár pedig egy általános gyulladás részeként.…”
Section: Acne Inversa: Miért Nem Acne éS Nem Is Hidradenitis?unclassified